PENGARUH KREATIVITAS PEMASARAN DAN PROMOSI ONLINE TERHADAP KINERJA PEMASARAN PENGRAJIN PATUNG GARUDA WISNU KENCANA DI DESA PAKUDUI KABUPATEN GIANYAR - Made Mulia Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2021)
Marketing creativity and online promotion are factors that affect marketing performance. The formulation of the problem in this study is: does marketing creativity and online promotion partially or simultaneously affect the marketing performance of the Garuda Wisnu Kencana sculpture craftsman in Pakudui Village, Gianyar Regency. The purposes of this study are: To determine the effect of marketing creativity and online promotion partially and simultaneously on the marketing performance of the Garuda Wisnu Kencana sculpture craftsman in Pakudui Village, Gianyar Regency. Gianyar Regency. The types of data used are quantitative and qualitative data. The data sources used are primary data and secondary data obtained from the marketing performance craftsmen of Garuda Wisnu Kencana sculpture craftsmen in Pakudui Village, Gianyar Regency. Sampling was done by using purposive sampling as many as 90 craftsmen. Data collection methods used are observation, interviews, questionnaires and documentation studies. Data were analyzed using classical assumption test, multiple linear regression analysis, analysis of determination, partial significance test (t-test) and simultaneous significance test (F-test). The results showed that there was a positive and partially significant effect between marketing creativity and online promotion on the marketing performance of the Garuda Wisnu Kencana sculpture craftsman in Pakudui Village, Gianyar Regency. Simultaneously, the results show that there is a simultaneous positive and significant influence between marketing creativity and online promotion on the marketing performance of the Garuda Wisnu Kencana sculpture craftsman in Pakudui Village, Gianyar Regency